Analysis of Temperature Transmitter Verification Using the Linear Current Method in Control Systems - Nico Karla Steven Purba; Hamdani Hamdani; Beni Satria (Sean Institute, 2026)
This study aims to analyze the verification process of temperature transmitters in control systems using the 4–20 mA linear current method. Temperature transmitters are a critical component in industrial instrumentation systems, converting temperature signals from sensors into analog current signals that can be processed by the control system. The accuracy of the transmitter output signal significantly impacts the performance of the process control system. The research method used is a verification method with a calibration approach and testing the linear relationship between the input resistance and the transmitter output current. Testing is carried out by varying the resistance value at several measurement points, then comparing the resulting output current value with the theoretical current value in the 4–20 mA range. The measurement data are then analyzed to determine the error value, percentage deviation, and linearity characteristics of the transmitter. Thus, the linear current method can be used as an effective approach in the process of verifying the performance of temperature transmitters in industrial control systems.